Nidana and Management of Lifestyle Disorders (International Journal of Ayurveda and Pharma Research, 2022)
Lifestyle disorders are the diseases linked with one’s lifestyle. Nowadays, lifestyle disorders are becoming more widespread and affecting a majority of the population and posing a huge public health threat around the world. According to the World Health Organization (WHO), lifestyle disorder is a subgroup of non-communicable diseases (NCDs) and accounts for around 71 percent of all deaths worldwide. Lifestyle disorders are caused mostly by poor diet and lack of physical activity. Distracting the people from physical exercise and their attraction towards sedentary lifestyle can lead to a variety of health problems including chronic non-communicable diseases with life-threatening issues. Hypertension, diabetes, PCOS, cancer, arthritis, obesity, insomnia, depression are the diseases which can be taken under lifestyle disorders. Ayurveda, science of life, aims in fundamental goal of maintaining health of healthy people and treatment of disease in sick one’s. To sustain a healthy and joyful life (Hitaayu & Sukhaayu), Ayurveda has a number of different principles and regimens including Ahara and Vihar (dietary habits and daily routine), Dinacharya (daily regimen), Ratricharya (night regimen), Ritucharya (seasonal regimen), Panchkarma (five detoxification and bio-purification therapies), Rasayana (rejuvenation), Sadvritta paalan (ideal habits) and Aachara Rasayana (code of conduct). Hence, lifestyle disorders can be well managed through Ayurveda by adopting its different principles and regimens.